2019
DOI: 10.1051/0004-6361/201935778
|View full text |Cite
|
Sign up to set email alerts
|

Merger induced clump formation in distant infrared luminous starburst galaxies

Abstract: While the formation of stellar clumps in distant galaxies is usually attributed to gravitational violent disk instabilities, we show here that major mergers also represent a competitive mechanism to form bright clumps. Using ∼ 0.1 resolution ACS F814W images in the entire COSMOS field, we measure the fraction of clumpy emission in 109 main sequence (MS) and 79 Herschel-detected starbursts (off-MS) galaxies at 0.5 < z < 0.9, representative of normal versus merger induced star-forming activity, respectively. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 119 publications
0
22
1
Order By: Relevance
“…Simulations and extrapolations from local studies suggest that the merger rate was high at z > 4 (e.g., Mantha et al 2018;Kohandel et al 2019) and targeted [CII] observations of normal z > 4 galaxies have revealed some galaxies with clumpy morphologies (Carniani et al 2018) which are likely caused by mergers (Calabrò et al 2019). But several observations have revealed evidence for ordered rotation (e.g., De Breuck et al 2014;Jones et al 2017;Smit et al 2018;Bakx et al 2020;Tadaki et al 2020), so the true distribution of kinematic states has been unknown.…”
Section: Morpho-kinematic Classificationmentioning
confidence: 99%
“…Simulations and extrapolations from local studies suggest that the merger rate was high at z > 4 (e.g., Mantha et al 2018;Kohandel et al 2019) and targeted [CII] observations of normal z > 4 galaxies have revealed some galaxies with clumpy morphologies (Carniani et al 2018) which are likely caused by mergers (Calabrò et al 2019). But several observations have revealed evidence for ordered rotation (e.g., De Breuck et al 2014;Jones et al 2017;Smit et al 2018;Bakx et al 2020;Tadaki et al 2020), so the true distribution of kinematic states has been unknown.…”
Section: Morpho-kinematic Classificationmentioning
confidence: 99%
“…We also intend to explore the region outside our two 10-kpc spheres, and evaluate the role of tidal compression in driving extended star formation (Renaud et al 2014(Renaud et al , 2015. These investigations can also be expanded into (1) the dwarf regime, where gas content and SFE might be substantially different (Stierwalt et al 2015;Pearson et al 2016;Kado-Fong et al 2020;Martin et al 2020) ; (2) the high-redshift regime, where modifications to ISM content and structure (Bournaud et al 2011;Fensch et al 2017;Calabrò et al 2019) are accompanied by an increased frequency of merging (Bluck et al 2009(Bluck et al , 2012López-Sanjuan et al 2009;López-Sanjuan et al 2012Rodriguez-Gomez et al 2015;Mantha et al 2018;Duncan et al 2019); (3) minor mergers, which are expected to be more frequent (Villalobos & Helmi 2008Qu et al 2011;Kaviraj 2014;Martin et al 2018); and (4) the massive regime, where mixed and dry encounters tend to appear (Lin et al 2008;Stewart et al 2009; Lin et al 2010) -and where AGN feedback and environmental quenching processes are likely to collaborate in concert with tidal interactions, and assist galaxies in achieving their retirement into the passive sequence (Bluck et al 2014(Bluck et al , 2020.…”
Section: S U M M a Rymentioning
confidence: 99%
“…This is a user-friendly Python implementation for the calculation of morphological statistics, described in detail by Rodriguez-Gomez et al (2019). It is largely based on previous work by Lotz et al (2004Lotz et al ( , 2006Lotz et al ( , 2008a) and has been thoroughly tested and applied in several independent studies (e.g., Calabrò et al 2019;Bignone et al 2020;Wu et al 2020).…”
Section: Methodsmentioning
confidence: 99%